23+(-9)-(-5)=

Simple and best practice solution for 23+(-9)-(-5)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 23+(-9)-(-5)= equation:


Simplifying
23 + (-9) + -1(-5) = 0
23 + -9 + -1(-5) = 0

Multiply -1 * -5
23 + -9 + 5 = 0

Combine like terms: 23 + -9 = 14
14 + 5 = 0

Combine like terms: 14 + 5 = 19
19 = 0

Solving
19 = 0

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| -5*(2t+3)=-5 | | 2s^3+11s^2+5s=0 | | 48x-80=8(6x-10) | | 2(x+16)=x+16 | | 5*(f-7)=0 | | y=2x^3-11x+15 | | 30a^7+16a^6+9a^8=0 | | (4x-9)/6-11/4 | | 6-5(1+8k)=19 | | -10*(s+1)=-14 | | (d-4)+2=2(d+2)-4 | | .5x=11 | | 4x-9/6-11/4 | | 13x-42=7x+12 | | 31x+26=31x+27 | | 5(10-3b)=105-b+4(11-4b) | | 6y+1=2y-7 | | 9x^4-4x^2+16=0 | | Y-3=1/2(x-8) | | 1.35/1=x/30 | | 3(8x+3)=24x-6 | | 40b^3+22b^2-6b=0 | | 3x+55=8x | | 0.56/1=x/23 | | -51+6x=-2x+53 | | 0.03/1=x/24 | | 7x+7y=29 | | x^2+10x+13=68 | | 0.16/1=x/1.875 | | 23456789+12345678909876543= | | -6=m/2-10 | | 6(3+9v)=-34 |

Equations solver categories